Annual Address to the Board of Governors, September 23, 1957 - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, spoke about the happenings in the Middle East which threatened to bring major economic dislocation and, at times, the world outlook had been bleak. He mentioned about the large amount lent by the Bank and important additions to its capital resources during the fiscal year 1957. He explained two loans for air transport that helped Australia and India to acquire the latest types of aircraft for their air lines. He concluded by saying that the Bank should make, over the years ahead, a continued and significant contribution to the capital requirements of basic development on which higher living standards depend.